2019
DOI: 10.1101/670620
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tetrodotoxin-sensitive sodium channels mediate action potential firing and excitability in menthol-sensitive Vglut3-lineage sensory neurons

Abstract: Small-diameter vesicular glutamate transporter 3-lineage (Vglut3 lineage ) dorsal root ganglion (DRG) neurons play an important role in mechanosensation and thermal hypersensitivity; however, little is known about their intrinsic electrical properties. We therefore set out to investigate mechanisms of excitability within this population. Calcium microfluorimetry analysis of male and female mouse DRG neurons demonstrated that the cooling compound menthol selectively activates a subset of Vglut3 lineage neurons.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…Intriguingly, we observed a new population of C-fibers with ongoing spike activity in the absence of externally applied thermal stimuli ( Figure 3B). These fibers are reminiscent of low-threshold cold receptors in the cornea (Belmonte et al, 2009) and may correspond to recently described mentholsensitive Vglut3 lineage sensory neurons described in vitro with ongoing activity (Griffith et al, 2019). The physiological properties of these fibers closely resembled thermally responsive units recorded in humans (Campero and Bostock, 2010;Campero et al, 2001), monkeys (Dubner et al, 1975), and rabbits (Shea and Perl, 1985).…”
Section: Ongoing Activity Of Cool-sensitive C-fibers At Physiologicalsupporting
confidence: 66%
See 1 more Smart Citation
“…Intriguingly, we observed a new population of C-fibers with ongoing spike activity in the absence of externally applied thermal stimuli ( Figure 3B). These fibers are reminiscent of low-threshold cold receptors in the cornea (Belmonte et al, 2009) and may correspond to recently described mentholsensitive Vglut3 lineage sensory neurons described in vitro with ongoing activity (Griffith et al, 2019). The physiological properties of these fibers closely resembled thermally responsive units recorded in humans (Campero and Bostock, 2010;Campero et al, 2001), monkeys (Dubner et al, 1975), and rabbits (Shea and Perl, 1985).…”
Section: Ongoing Activity Of Cool-sensitive C-fibers At Physiologicalsupporting
confidence: 66%
“…The loss of warm sensation in trpm8 À/À mice could be an indirect consequence of the early developmental loss of cool information reaching the brain. We addressed this issue by acutely inactivating TRPM8 in the forepaw of WT mice using PBMC (1-Phenylethyl-(2-aminoethyl)[4-(benzyloxy)-3-methoxybenzyl]carbamate), a selective antagonist of TRPM8 that has been shown to suppress cooling-responsive cells and reduce cooling-evoked behavioral responses in mice (Gonzá lez et al, 2017;Griffith et al, 2019;Knowlton et al, 2013;Yudin et al, 2016). We first trained WT animals to report warm stimuli and then we pharmacologically inactivated TRPM8 by performing a transdermal injection in the plantar side of the right forepaw ( Figures 6D-6F).…”
Section: Articlementioning
confidence: 99%
“…RNAscope analysis was performed using the ACDbio RNAscope kit for nonfixed tissue (ACD #320851) based on ref. 71 . In short, DRG extracted from adult mice were fixed for 15 min in 4% PFA, washed in PBS, and allowed to equilibrate in 30% sucrose for 2 h before embedding in OCT (Tissue Tek; Sakura Finetek).…”
Section: Methodsmentioning
confidence: 99%
“…Cre-driver lines were crossed with mouse reporter lines that express membrane-bound GFP (Hippenmeyer et al, 2005; Muzumdar et al, 2007). We found that trigeminal ganglion neurons were labeled with three different Cre markers ( Figure 3A) : the GDNF receptor Ret (Ret CreERT2 tamoxifen-induced at P21–30), vesicular glutamate transporter 3 ( Vglut3 Cre ) and the NGF receptor Ntrk3 CreERT2 (tamoxifen-induced at P21–30; (Bai et al, 2015; Griffith et al, 2019; Grimes et al, 2011; Lou et al, 2013; Luo et al, 2009). We quantified expression of each marker in the trigeminal ganglion and found that Ret CreERT2 labeled 31% of trigeminal neurons, Vglut3 Cre labeled 29% of trigeminal neurons, and Ntrk3 CreERT2 labeled 10% of trigeminal neurons.…”
Section: Resultsmentioning
confidence: 99%